2000
DOI: 10.1054/bjoc.2000.1492
|View full text |Cite
|
Sign up to set email alerts
|

Phase I clinical trial with IL-2-transfected xenogeneic cells administered in subcutaneous metastatic tumours: clinical and immunological findings

Abstract: Summary Various studies have emphasized an immunodepression state observed at the tumour site. To reverse this defect and based upon animal studies, we initiated a phase I clinical trial of gene therapy in which various doses of xenogeneic monkey fibroblasts (Vero cells) genetically engineered to produce human IL-2 were administered intratumorally in 8 patients with metastatic solid tumours. No severe adverse effect was observed in the 8 patients analysed during this clinical trial even in the highest dose (5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…By having cytokine production that is still under the homeostatic control of the host, cytokine-gene activators might carry more beneficial safety profiles than their protein counterparts (Gillis and Williams, 1998). In fact, Tartour et al (2000), have reported that in a phase I clinical trial of gene therapy in which various doses of xenogeneic monkey fibroblasts (Vero cells) genetically engineered to produce human IL-2 were administered intratumorally in eight patients with metastatic solid tumors and no severe adverse effect was observed in the eight patients analyzed during this clinical trial even in the highest dose group. Another therapeutic approach is utilization of IL-2 inducing agents in order to stimulate the patient's body to produce IL-2.…”
Section: Resultsmentioning
confidence: 99%
“…By having cytokine production that is still under the homeostatic control of the host, cytokine-gene activators might carry more beneficial safety profiles than their protein counterparts (Gillis and Williams, 1998). In fact, Tartour et al (2000), have reported that in a phase I clinical trial of gene therapy in which various doses of xenogeneic monkey fibroblasts (Vero cells) genetically engineered to produce human IL-2 were administered intratumorally in eight patients with metastatic solid tumors and no severe adverse effect was observed in the eight patients analyzed during this clinical trial even in the highest dose group. Another therapeutic approach is utilization of IL-2 inducing agents in order to stimulate the patient's body to produce IL-2.…”
Section: Resultsmentioning
confidence: 99%
“…Our study confirms the favorable toxicity profile of Vero -IL -2 treatment seen in the two phase I studies reported previously. 11,12 In addition, although we did not see a single PR or CR, 14 of 28 patients ( 50% ) achieved SD lasting for up to 4 months. This observation can by no means be taken as proof of the clinical efficacy of Vero -IL -2.…”
Section: Discussionmentioning
confidence: 66%
“…36 Interestingly, in our two phase I studies, the most important clinical and immunological responses occurred at the two lower dose levels using Vero -IL -2 cells producing relatively high amounts of 14,000 U per 10 5 cells per day. 11,12 Although our results in humans cannot be quantitatively compared to those by Schmidt et al for various biological and technical reasons, it can be speculated that the ''bell -shaped dose response curve'' to IL -2 described in animals might indeed also play a role in clinical trials in humans. For that reason, we had designed our phase II study as a randomized comparison of two dose levels, but the lack of efficiency of TG2001 in our study makes any conclusion on a dose -response effect of IL -2 impossible.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Vaccinia virus (VV) was chosen because its virology and safety are well described. Similarly, IL-2 was selected because it has demonstrated powerful effects in some animal models, 5 and in human clinical trials, [6][7][8] including MM.…”
mentioning
confidence: 99%